PENGARUH DOSIS HEMODIALISIS TERHADAP KEJADIAN ASCITES PADA PASIEN GAGAL GINJAL KRONIS YANG MENJALANI HEMODIALISIS DI RST dr. SOEDJONO MAGELANG: EFFECT OF HEMODIALYSIS DOSE ON ASCITES EVENT IN CHRONIC RENAL FAILURE PATIENTS TREATING HEMODIALYSIS IN RST dr. SOEDJONO MAGELANG - Endro Haksara; Ainnur Rahmanti (JURNAL KEPERAWATAN SISTHANA, 2021)
Chronic renal failure is a progressive and continuous destruction of kidney structures. Chronic renal failure occurs in susceptible individuals, analgesic nephropathy, destruction of renal papillae associated with daily use of analgesic drugs for years. Whatever the cause, there is a progressive deterioration of kidney function which is characterized by a progressive decrease in the Glomelurus Filter Rate (GFR) (Corwin, 2009). Chronic kidney failure is a failure of kidney function to maintain metabolism and fluid and electrolyte balance due to progressive destruction of kidney structures with manifestations of accumulation of residual metabolites (uremic toxicants) in the blood (Muttaqin & Sari, 2011). as well as electrolytes and acid-base composition of body fluids, removing metabolic wastes that are no longer needed by the body, regulating blood pressure and hormonal function. Chronic Kidney Disease (CKD) is the final stage of chronic kidney failure where GFR <15 ml/min/1.73m2 so that the body fails to maintain metabolism and fluid and electrolyte balance, causing uremia, namely retention of urea and other nitrogenous wastes in the blood (Smeltzer et al. al, 2008; National Kidney Foundation in Kallenbach, et al, 2005). With the increasingly real decline in kidney function or worsening of symptoms of uremia, renal replacement therapy is required for survival, namely dialysis and organ transplantation. There are two methods of dialysis, one of which is Hemodialysis (Potter, 2005; Smelzer, 2008).